الهجرة غير الشرعيّة من المغرب نحو أسبانيا أسبابها وآثارها - قنوع نزار; خربوط مجد; طيبا سـحر أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يتناول هذا البحث دراسة لقضية تعتبر من أهمّ القضايا المعاصرة بالنسبة لجميع دول العالم عموماً, ودول حوض المتوسط خصوصاً, هذه القضية هي ظاهرة الهجرة غير الشرعيّة في المغرب, نتيجة لما تتضمنه من سلبيات, ومنها المصير المجهول للمهاجرين غير الشرعيّين، سواء بالموت غرقاً, أم السجن على يد سلطات الدول المهاجر إليها. الاهتمام بهذه الظاهرة الآن والسعي للحدّ منها بمعالجة أسبابها هو المحور الرئيسي للدراسة المقدمة. حيث يتناول البحث العناوين الرئيسيّة التالية, الأول محور الشباب بين الواقع والطموح وفيه نتناول تعريف الظاهرة, ودراسة أسبابها, امّا الثاني فيتناول المغرب كبلد مصدر للعمالة, وفيه نتناول توزيع المغاربة في العالم وآثار الظاهرة, والثالث يتناول تدابير الحدّ من الظاهرة في كل من المغرب وأوروبا, وصولاً لتقديم بعض المقترحات التي من شأنها أن تسهم في الحدّ منها. This research studies one of the most important contemporary issues for all countries of the world in general, and the Mediterranean countries in particular, this case is the phenomenon of illegal immigration in Morocco, as a result of Provisions of the downsides, including the unknown fate of illegal immigrants, whether death by drowning, or imprisonment at the hands of the authorities of destination countries. Attention to this phenomenon now and seek to reduce them to address their causes is the main focus of the study provided. Where deals Find the following main headings, the first axis of young people between reality and ambition, where we take the definition of the phenomenon, and the study of its causes, while the second deals with Morocco as a source of employment, in which we address the distribution of Moroccans in the world and the effects of the phenomenon, and the third deals with measures to limit the phenomenon in Morocco and Europe, down to make some proposals that would contribute to the reduction.